Review of active power filter technologies - Zainal, Salam, Prof. Dr.; Tan, Perng Cheng; Awang, Jusoh, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/